Spanish Tipsters and the Millennial and Centennial Generations in the Scenario of a Pandemic - Barrientos-Báez, Almudena (2022)
The growth and popularization of sports betting have led to the emergence of a new type of influencer: Tipsters, people and betting houses who influence and advise through social networks on the bets they consider most profitable. Both agents are also content-generating, forming a particular ecosystem with a specific narrative. The research examines the narratives of both the personal and betting houses profiles that make up the category of tipsters and their impact on younger generations. It also takes an in-depth look at the content and languages used by tipsters on social media and what determines their success in terms of followers and interactions. The period and place analyzed is the year 2020 in Spain, because it allows observing the differences between the periods of free transit and the quarantine period caused by Covid-19. The selection of the studied profiles is based on the five most recommended profiles, according to 10 rankings in the sports betting sector. The results show how the tipsters’ narrative was adapted to the context of the pandemic to maintain interest during the quarantine and not lose its influence towards millennials and centennials. Especially relevant is the period after the quarantine, with long periods of stay at home by young people, where the narrative has iconic, symbolic, and linguistic elements typical of war periods.